Metaphors of winter natural phenomena in Lithuanian and Russian poetic texts - Jasiūnaitė, Birutė; Konickaja, Jelena (Lietuvių kalba, 2019)
The present article is devoted to metaphors of winter natural phenomena, that is frost, ice and hoarfrost, in Lithuanian and Russian poetic texts that mainly come from the 20th century. The metaphors have been identified on the basis of poetry collections, anthologies, children’s poetry and the Russian language corpus (363 metaphors in total from 53 Russian and 44 Lithuanian poets’ works). The researchers rely on previous experience in the analysis of metaphors of natural phenomena. Thus, the article considers five groups of metaphors: 1) a natural phenomenon is a living creature or a part of it; 2) frost, ice and hoarfrost are objects (phenomena) of inanimate nature; 3) a winter phenomenon is an object from the social sphere; 4) frost, ice and hoarfrost are abstract objects; 5) some other metaphors. The comparison of the metaphors in two poetic languages has shown both significant similarities and striking differences. The similarity consists in the fact that subject metaphors are most often utilized in poetic texts, as well as anthropomorphic, zoomorphic and biomorphic metaphors. The differences are explained by the lack of metaphors in one of the systems that are presented in the other one, for instance, in Lithuanian poetry there are no metaphors of ‘frost’ as smoke and ‘ice’ as mica, while Russian poets do not use metaphors, such as ‘a winter phenomenon of nature’ is a means for lighting, or ‘icicles’ are a clock that is characteristic of Lithuanian poetry. In Russian poetry, there is a branching group where ‘a winter phenomenon’ is metal, a precious stone, and in Lithuanian poetry there is a group of ‘frost (ice, hoarfrost)’ that is a sharp cutting object. The differences between the two poetic systems are also associated with connotations: in Russian poetry, unlike Lithuanian, metaphors of winter natural phenomena quite often have positive connotations. At the end of the article, a scheme is presented that reflects the results of the analysis.